1976
DOI: 10.1007/bf03005682
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on baroreceptor reflex function in man

Abstract: IT IS WELL KNOWN that baroreceptor reflex activity is an important factor in the acute homeostatic regulation of the cardiovascular system, particularly under stressful conditions such as haemorrhage or sudden postural changes. 1-4 Despite the numerous changes observed in cardiovascular structure and function that occur with aging, 5-13 the relationship between aging and baroreceptor reflex function has not been clarified. Earlier work by Norris, et al. TM using tilting techniques observed reflex changes in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(7 citation statements)
references
References 44 publications
(3 reference statements)
0
6
1
Order By: Relevance
“…Therefore, pentobarbital anesthesia does not seem to affect the G value. The results of this study differ from the general assumption found in the literature that baroreceptor sensitivity declines with aging (GRIBBIN et al, 1971;FROLKis et al, 1975;DUKE et al, 1976;VLACHAKis et al, 1976;RANDALL et al, 1978). Earlier studies, however, were based on the relationship between heart period and systolic arterial pressure changes in response to intravenous injection of pressor agents.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, pentobarbital anesthesia does not seem to affect the G value. The results of this study differ from the general assumption found in the literature that baroreceptor sensitivity declines with aging (GRIBBIN et al, 1971;FROLKis et al, 1975;DUKE et al, 1976;VLACHAKis et al, 1976;RANDALL et al, 1978). Earlier studies, however, were based on the relationship between heart period and systolic arterial pressure changes in response to intravenous injection of pressor agents.…”
Section: Discussioncontrasting
confidence: 99%
“…It is well known that, in the elderly, cardiac function is well maintained at rest, but its ability to adjust to environmental changes is reduced compared to younger individuals [1]. For example, the cardiac response to changes in blood pressure (baro-reflex) decline with advancing age [2,3] as a result of reduced sensitivity of baroreceptors [4][5][6].Cardiac responses to changes in the external environment, such as the bradycardia that results from exposure of the face to cold temperatures, also decrease with age [7], though the mechanism by which this occurs remains to be elucidated. It has been reported that nociceptive stimulation of the skin in anesthetized adult animals results in a reflexive increase in HR that Japanese Journal of Physiology, 54, 137-141, 2004 Key words: heart rate, cardiac sympathetic nerve, somatocardiac reflex, aging, ␤-adrenergic receptor.…”
mentioning
confidence: 99%
“…It is well known that, in the elderly, cardiac function is well maintained at rest, but its ability to adjust to environmental changes is reduced compared to younger individuals [1]. For example, the cardiac response to changes in blood pressure (baro-reflex) decline with advancing age [2,3] as a result of reduced sensitivity of baroreceptors [4][5][6].…”
mentioning
confidence: 99%
“…To the contrary, it has been reported that baroreflex function decreased with aging in man [5,7,9,20] . In most these investigations, the effects of aging on baroreflex function were estimated from relationship between heart rate and systemic AP changes in response to vasoactive drugs, which does not mean baroreflex control of AP.…”
mentioning
confidence: 98%
“…Effects of aging on arterial pressure (AP) control system have often been assessed from responses of AP to vasoactive drugs [5,7,9,19,20] or to exercises [2,14,18,211. Most of these studies showed physiological alteration of the AP control system with aging when the responses were recorded even in a short period of time under unanesthetized conditions.…”
mentioning
confidence: 99%